Im Spannungsfeld brutalistischer Strömungen und Liturgischer Bewegung - Bauten der Nachkriegsmoderne von Klaus Franz - Busse, Anette S. (KIT Scientific Publishing, 2020)
The development of art in the early 20th century fertilized architecture, the discourse of which increasingly influenced church construction, which produced a high creative density within the clearly defined program and developed a surrogate of theoretical-religious and architectural-modern forms. This development spurred a technical and scientific breakthrough of complex form-building insights, whose form-finding and ordering principles were transferred to architecture.